Effect of a helium and oxygen mixture on physiological parameters of rats with cerebral arterial air embolism - Palikov, V. A.; Pavlov, N. B.; Amirov, R. R.; Ismailova, A. M.; Borozdina, N. A.; Palikova, Yu. A.; Dyachenko, I. A.; Khokhlova, O. N.; Ponomareva, T. I.; Rykov, V. A.; Logunov, A. T.; Murashev, A. N.; et al. (Frontiers in Physiology, 2024)
Cerebral arterial air embolism (CAE) is a serious and potentially dangerous condition that can interrupt the blood supply to the brain and cause stroke. One of the promising gas mixtures for emergency treatment of air embolism is an oxygen-helium mixture. We modeled CAE in awake rats by injecting air into the common carotid artery. Immediately after CAE, animals were either untreated or underwent hyperbaria, oxygen inhalation, heated air inhalation, or helium-oxygen mixture inhalation. Body temperature, locomotor activity, respiratory and cardiovascular parameters were monitored in the animals before CAE modeling, and 3 and 24 hours after CAE modeling. After 3 hours of CAE modeling in awake rats, depression of the nervous, cardiovascular and respiratory systems, as well as decreased body temperature were observed. 24 hours after CAE modeling multifocal cerebral ischemia was observed. Normobaric helium-oxygen mixture inhalation, on par with hyperbaric treatment, restored body temperature, locomotor activity, respiratory volume, respiratory rate, and blood pressure 3 hours after CAE, and prevented the formation of ischemic brain damage lesions 24 hours after CAE. Thus, inhalation of a heated oxygen-helium gas mixture (O2 30% and He 70%) immediately after CAE improves the physiological condition of the animals and prevents the foci of ischemic brain damage formation.